Improving the soft X‐ray reflectivity of Cr/Ti multilayers by co‐deposition of B4C. (9th October 2020) - Zhu, Jingtao; Zhang, Jiayi; Li, Haochuan; Tu, Yuchun; Chen, Jinwen; Wang, Hongchang; Dhesi, Sarnjeet S.; Cui, Mingqi; Zhu, Jie; Jonnard, Philippe
Abstract : Systematic analysis on interfaces of Cr/Ti multilayers has been performed. The near‐normal‐incidence reflectivity increases from 4.48% to 15.75% at a wavelength of 2.73 nm using co‐deposition of B4 C. Abstract : The `water window', covering 2.4–4.4 nm, is an important wavelength range particularly essential to biology research. Cr/Ti multilayers are one of the promising reflecting elements in this region because the near‐normal‐incidence reflectivity is theoretically as high as 64% at 2.73 nm. However, due to multilayer imperfections, the reported reflectivity is lower than 3% for near‐normal incidence. Here, B and C were intentionally incorporated into ultra‐thin Cr/Ti soft X‐ray multilayers by co‐deposition of B4 C at the interfaces. The effect on the multilayer structure and composition has been investigated using X‐ray reflectometry, X‐ray photoelectron spectroscopy, and cross‐section electron microscopy. It is shown that B and C are mainly bonded to Ti sites, forming a nonstoichiometric TiB x C y composition, which hinders the interface diffusion, supresses the crystallization of the Cr/Ti multilayer and dramatically improves the interface quality of Cr/TiB x C y multilayers. As a result, the near‐normal‐incidence reflectivity of soft X‐rays increases from 4.48% to 15.75% at a wavelength of 2.73 nm.